Urban agglomeration and the aggregate economic growth - Domingo Pérez Ximénez-De-Embún; Marcos Sanso (European Regional Science Association (ERSA), 2011)
This paper presents a theoretical approach to solve the main problems faced to explain the relationship between aggregate economic growth and the urban structure. The most significant conclusion reached is that there is a theoretical relationship between aggregate economic growth and urban concentration with an inverted-U shape. This result had been previously found in an empirical context (Henderson, 2003), but not as outcome of a theoretical model. An overlapping generations model with four different types of goods (some with both technological and local externalities) and two cities where their production could be located provides the dynamics of the movements of labor and goods across cities. The resulting system of two cities with different patterns of specialization, urban concentration and economic growth rates, makes clear how to set out the comparison of aggregate growth rates: only the aggregate growth rate between two steady states, one without migration but with trade specialization and the other after migration and specialization, makes sense. Henderson, V. (2003), The Urbanization Process and Economic Growth: The So-What Question, Journal of Economic Growth, 8, 47-71.
Keywords: 330